Stability of empty and peptide-loaded class II major histocompatibility complex molecules at neutral and endosomal pH: comparison to class I proteins. - Reich, Z; Altman, J; Boniface, J; Lyons, D; Kozono, H; Ogg, G; Morgan, C; Davis, M (1997)
The structure and thermal stability of empty and peptide-filled forms of the murine class II major histocompatibility complex (MHC) molecule I-E(k) were studied at neutral and mildly acidic pH. The two forms have distinct circular dichroic spectra, suggesting that a conformational change may accompany peptide binding. Thermal stability profiles indicate that binding of peptide significantly increases the thermal stability of the empty heterodimers at both neutral and mildly acidic pH. Free energies calculated from these data provide a direct measure of this stabilization and show that the empty form of I-E(k) is significantly more stable than that of class I MHC proteins. Furthermore, for the two MHC class II proteins that were analyzed (I-E(k) and I-A(d)), thermal stability was not significantly altered by acidification. In contrast, of four class I MHC molecules studied, three have shown a significant loss in complex stability at low pH. The marked stability exhibited by their empty form, as well as their resistance to low pH, as observed in this study, correlate well with the ability of class II MHC molecules to traverse and bind peptides in acidic endosomal vesicles.